Improving interprofessional collaboration: The effect of training in nonviolent communication. (2nd July 2016) - Museux, Anne-Claire; Dumont, Serge; Careau, Emmanuelle; Milot, Élise
ABSTRACT: This article examines the effects of nonviolent communication (NVC) training on the interprofessional collaboration (IPC) of two health and social services sector care teams. The study was conducted in 2013 with two interprofessional teams ( N  = 9) using a mixed method research design to measure the effects of the training. Individual IPC competency was measured using the Team Observed Structured Clinical Encounter tool, and group competency using the Observed Interprofessional Collaboration tool. A focus group was held to collect participant perceptions of what they learned in the training. Results revealed improvements in individual competency in client/family-centered collaboration and role clarification. Improvements in group competency were also found with respect to teams' ability to develop a shared plan of action. Data suggests that participants accepted and adopted training content. After the training, they appeared better able to identify the effects of spontaneous communication, more understanding of the mechanisms of empathy, and in a better position to foster collective leadership.